Morphometric Characterization of the Akbaş (Akbash) Turkish Shepherd Dog - Milivoje Urosevic; Darko Drobnjak; Petar Stojic; Yusuf Ziya Oğrak (Turkish Journal of Agriculture: Food Science and Technology)
In this study, a morphometric investigation was carried out on the Akbash Turkish shepherd dog breed using 30 exterior parameters. The study consisted of 96 dogs (54 males and 42 females) ranging in age from 2 to 9 years. All dogs were bred in the West Anatolia region of Turkey, around the city of Eskisehir. The following exterior parameters were measured and their means were obtained: height at withers (65.22±3.99 cm), height at mid-back (62.24±4.24 cm), height at rump (64.97±4.16 cm), height at base of tail (58.2±5.01 cm), height to elbow (36.07±4.06 cm), height to knee (35.83±4.96 cm), height to hock (17.08±3.21 cm), height to tip of sternum (45.12±4.30 cm), body length (70.58±5.58 cm), chest depth (29.58±3.23 cm), chest width (21.02±3.18 cm), breast width (16.86±3.41 cm), chest circumference (77.86±7.05 cm), pastern circumference (13.27±1.67 cm), rump length (19.21±3.27 cm), pelvic width (8.65±2.18 cm), rump protuberance width (7.58±3.02 cm), head length (27.20±2.85 cm), skull length (16.58±1.92 cm), muzzle length (10.30±2.35 cm), skull width (14.06±1.96 cm), muzzle width (7.60±1.26 cm). According to the obtained morphological characteristics the dog has a rectangular body format, and the rump is somewhat higher than the height at the withers. According to its craniological characteristics it belongs to the group of mesaticephalic dogs. The width of the skull is smaller than its length. Angles of the hind legs are more open than angles of the front legs.